Volume 8: Seismic Engineering 2015
DOI: 10.1115/pvp2015-45123
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Analysis of Coupled Support Structures and Piping Systems Subject to Seismic Loading

Abstract: The prevailing lack of proper and uniform seismic design guidelines for piping systems impels designers to follow standards conceived for other structures, such as buildings. The modern performance-based design approach is yet to be widely adopted for piping systems, while the allowable stress design method is still the customary practice. This paper presents a performance-based seismic analysis of petrochemical piping systems coupled with support structures through a case study. We start with a concept of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Although EN and AM codes of pipelines design do not make reference of shell elements yet only to beam ones, the last type of element may be incapable of capturing the exact strain-stress response [7]. In view of the large model under investigation and the availabilities of the analysis software [27] for pipe modelling, stick models both for straight and curved pipe have been used and calibrated according to [32]. It is worth mentioning that the internal operating pipe pressure is low (Pmax=1.63 MPa) as quoted in [30] and thus neglected in order to remain on the safe side since the pressure increases at low operating levels the bending stiffness of pipe bends ( [32]).…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EN and AM codes of pipelines design do not make reference of shell elements yet only to beam ones, the last type of element may be incapable of capturing the exact strain-stress response [7]. In view of the large model under investigation and the availabilities of the analysis software [27] for pipe modelling, stick models both for straight and curved pipe have been used and calibrated according to [32]. It is worth mentioning that the internal operating pipe pressure is low (Pmax=1.63 MPa) as quoted in [30] and thus neglected in order to remain on the safe side since the pressure increases at low operating levels the bending stiffness of pipe bends ( [32]).…”
Section: Model Descriptionmentioning
confidence: 99%
“…In view of the large model under investigation and the availabilities of the analysis software [27] for pipe modelling, stick models both for straight and curved pipe have been used and calibrated according to [32]. It is worth mentioning that the internal operating pipe pressure is low (Pmax=1.63 MPa) as quoted in [30] and thus neglected in order to remain on the safe side since the pressure increases at low operating levels the bending stiffness of pipe bends ( [32]). The pipelines are supported mainly in a flexible way on the rack by keeping free the displacement in the axial direction of the pipe as well as all the degrees of freedom.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Probabilistic fire analyses and fragility curves become even more rare when it comes to industrial and petrochemical plants, though their piping systems mainly transport flammable material, liquid or gas fuel. Natural or accidental events may severely damage the structure supporting the piping systems [27][28][29][30][31][32], usually consisting of steel pipe-racks, and they may cause a release of flammable material from a pipe or a tank. Although in general the probability of occurrence of a fire may be low, the probability of ignition of the spilled flammable material increases in industrial environments and severe consequences are expected, as shown, among the others, by Uehara [33], Chan and Lin [34],…”
Section: Introductionmentioning
confidence: 99%
“…Phan et al [7] analysed the seismic vulnerability of an elevated steel storage tank supported by reinforced concrete columns, by developing a probabilistic demand model. Numerous seismic analyses were performed on petrochemical piping systems and their support structure by Paolacci et al [8]- [12]. They namely considered an existing steel pipe rack as case study and delivered performance-based seismic analyses.…”
Section: Introductionmentioning
confidence: 99%